The expression of powdery mildew resistance in spring bread wheat cultivars from the VIR collection of plant genetic resources - T. V. Lebedeva; E. V. Zuev; A. N. Brykova (Труды по прикладной ботанике, генетике и селекции)
Background. Powdery mildew caused by Blumeria graminis (DC.) E.O. Speer f. sp. tritici Em. Marchal. is a widespread foliar disease of common wheat in regions with cool and wet conditions. The disease infects the foliage, stem and spike of the wheat host. The most economical and environmentally safe method for controlling powdery mildew is the development of resistant bread wheat cultivars. The objective of this work was to analyze wheat (Triticum aestivum L.) cultivars for resistance to a powdery mildew population.Materials and methods. The VIR collection of plant genetic resources is a rich source of genetic materials. The study of resistance to the fungus employed 465 common wheat cultivars. The plants were inoculated at the seedlings, heading and flowering stages of plant development. The population of fungus was virulent to Pm1, Pm2, Pm3a-d, Pm4a-b, Pm5a, Pm6, Pm7, Pm8, Pm9, Pm16, Pm19 and avirulent to Pm12. For the estimation of plant damage, a scale from 0 (no damage) to 4 (abundant pustules) was used.Results and conclusions. The estimation of powdery mildew resistance was made in the field on adult plants. Out of 465 cultivars, resistant accessions amounted to 10,5%, intermediate ones to 16.8%, and susceptible ones to 72.7%. Generally, the resistant varieties originated from Europe and Russia. The group of the resistant cultivars (adult plants) was inoculated with fungus at the seedling stage and the plant damage was estimated. The cultivars 'Kandela', 'Arabeska', 'Batalj', 'Stillet' were resistant at all growth stages. The genetic control of powdery mildew resistance at different wheat growth stages was discussed.